The impact of yeast presence in nectar on bumble bee behavior and fitness. Issue 1 (19th November 2019) - Pozo, María I.; van Kemenade, Gaby; van Oystaeyen, Annette; Aledón‐Catalá, Tomás; Benavente, Alfredo; Van den Ende, Wim; Wäckers, Felix; Jacquemyn, Hans
Abstract: The presence of yeasts in pollen and floral nectar is rather the norm than the exception. Due to the metabolic activities of yeasts, sugar and amino acid composition of nectar often drastically change and may negatively impact the nutritional value of nectar for pollinators and hence insect fitness. On the other hand, the presence of yeasts in floral nectar may also increase its nutritional value due to yeast's probiotic effect and the release of yeast's metabolites. In this study, we investigated whether the presence of defined flower‐ and insect‐associated yeasts affected individual and colony fitness of the bumble bee pollinator Bombus terrestris . Specifically, we tested whether the presence of yeasts in nectar affected bumble bee foraging behavior and nectar consumption, individual growth and colony development, larval and queen mortality, and mating success. Quantitative analyses of sugar and amino acid profiles showed that nectar yeasts significantly affected the chemical composition of nectar. However, dual‐choice experiments indicated that yeast inoculation did not significantly affect foraging behavior or consumption rates. Nest development, on the other hand, was significantly affected by the presence of yeasts, but effects largely depended on species identity, with Candida bombiphila, Metschnikowia gruessii, and Rhodotorula mucilaginosa having the largest positive impact on colony growth. Interestingly, the effects at the colony level were more pronounced than at the individual level. In vitro growth tests further showed that yeasts have the potential to suppress the growth of the bumble bee gut pathogen Crithidia bombi . Overall, these results demonstrate that nectar‐inhabiting yeasts can have diverse effects on bumble bee fitness and therefore may mediate plant–pollinator mutualisms.